Multisector intervention to accelerate reductions in child stunting: an observational study from 9 sub-Saharan African countries - Remans, Roseline; Pronyk, Paul M; Fanzo, Jessica C; Chen, Jiehua; Palm, Cheryl A; Nemser, Bennett; Muniz, Maria; Radunsky, Alex; Abay, Alem Hadera; Coulibaly, Mouctar; Mensah-Homiah, Joseph; Wagah, Margaret; et al. (The American journal of clinical nutrition, 2011)
In sub-Saharan Africa, ~ 40% of children <5 y old are stunted, with levels that have remained largely unchanged over the past 2 decades. Although the complex determinants of undernutrition are well recognized, few studies have evaluated strategies that combine nutrition-specific, health-based approaches with food system- and livelihood-based interventions. We examined changes in childhood stunting and its determinants after 3 y of exposure to an integrated, multisector intervention and compared these changes with national trends. A prospective observational trial was conducted across rural sites in 9 sub-Saharan African countries with baseline levels of childhood stunting >20%. A stratified random sample of households and resident children <2 y old from villages exposed to the program were enrolled in the study. Main outcome measures included principal determinants of undernutrition and childhood stunting, which was defined as a height-for-age z score less than -2. National trends in stunting were generated from demographic and health surveys. Three years after the start of the program in 2005-2006, consistent improvements were observed in household food security and diet diversity, whereas coverage with child care and disease-control interventions improved for most outcomes. The prevalence of stunting in children <2 y old at year 3 of the program (2008-2009) was 43% lower (adjusted OR: 0.57; 95% CI: 0.38, 0.83) than at baseline. The average national stunting prevalence for the countries included in the study had remained largely unchanged over the past 2 decades. These findings provide encouraging evidence that a package of multisector interventions has the potential to produce reductions in childhood stunting.